2016
DOI: 10.11152/mu.2013.2066.181.xzi
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to assessing fetal tissue stiffness using virtual touch tissue quantification.

Abstract: Aims: Virtual touch tissue quantification (VTTQ) has been widely used in adults, but its application in fetuses has not been reported. The purposes of this study were to describe the normal shear wave velocity (SWV) values of fetal brain, lung, and liver by VTTQ and to examine the clinical usefulness of this procedure in evaluation of gestational age-related SWV changes in the fetal brain, lung and liver. Material and methods: One hundred fetuses were enrolled in this study and were evaluated at 18 weeks (seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 21 publications
(25 reference statements)
2
12
2
Order By: Relevance
“…The quantitative elastography confirmed that hepatic tissue has a greater stiffness than lung tissue (mean SWV 0.98 ± 0.12 and 0.84 ± 0.11 m/s, respectively), and the values obtained in the present study may be used as reference ranges in future clinical studies. The values of the SWV of the foetal lung and liver tissues of dogs are similar to the corresponding human SWV values (mean 1.05 ± 0.49 and 1.09 ± 0.24 m/s, respectively) during the second (18 weeks) and third trimester (35 weeks) of pregnancy and do not differ between the trimesters (P > 0.05), as reported by Zheng et al (2016). In contrast to Zheng et al (2016) and the findings in the present study, Quarello et al (2016) evaluated the second half of baboon pregnancy every 4 weeks during a 9-month period, using real-time duplex B-mode elastography color-coded image techniques in which post-processing software sets the tissue stiffness in kilopascals.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The quantitative elastography confirmed that hepatic tissue has a greater stiffness than lung tissue (mean SWV 0.98 ± 0.12 and 0.84 ± 0.11 m/s, respectively), and the values obtained in the present study may be used as reference ranges in future clinical studies. The values of the SWV of the foetal lung and liver tissues of dogs are similar to the corresponding human SWV values (mean 1.05 ± 0.49 and 1.09 ± 0.24 m/s, respectively) during the second (18 weeks) and third trimester (35 weeks) of pregnancy and do not differ between the trimesters (P > 0.05), as reported by Zheng et al (2016). In contrast to Zheng et al (2016) and the findings in the present study, Quarello et al (2016) evaluated the second half of baboon pregnancy every 4 weeks during a 9-month period, using real-time duplex B-mode elastography color-coded image techniques in which post-processing software sets the tissue stiffness in kilopascals.…”
Section: Discussionsupporting
confidence: 84%
“…In veterinary medicine, the ARFI ultrasonographic technique has been used to detect various pathological changes in the canine and spleen and kidneys of cats as well as in the liver, prostate gland, and testes of dogs (Holdsworth et al, 2014;Feliciano et al, 2015a, b;Garcia et al, 2015;Maronezi et al, 2015). This technique also promises to be a valid method of assessing structural changes in foetal lungs and liver that may be indicative of the maturation; previous studies by Quarello et al (2016) in baboons and by Zheng et al (2016) in humans defined the normal ranges for foetal lung shear wave velocity during gestational development. There, however, have been no earlier systematic studies in humans or animal species of veterinary interest using foetal pulmonary and hepatic elastography during the prenatal period.…”
Section: Introductionmentioning
confidence: 99%
“…Data on intrauterine elastographic evaluation of foetal tissues are very limited, with a few studies available in the literature using baboon foetuses as an experimental model (Quarello, Lacoste, Mancini, Melot‐Dusseau, & Gorincour, ,b; Quarello et al., ) and a single study evaluating human foetuses (Zheng, Wu, & Tan, ). These studies demonstrated the feasibility, reproducibility and applicability of elastography in the evaluation of maternal and foetal tissues, revealed important information about normal elasticity standards, however, have shown only weak correlation between elastography variables and gestational development.…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic radiation force impulse (ARFI) elastography is an ultrasound imaging technique used for the assessment of tissue elasticity (Feliciano et al, 2014). Recent studies have shown that this technique is both applicable and viable for the assessment of fetal pulmonary tissue in baboons (Quarello et al, 2016), humans (Zheng et al, 2016), dogs (Simões, 2016), and sheep (Silva, 2017). The observed parameters also correlate with the gestational development of these species.…”
Section: Introductionmentioning
confidence: 99%